2022
DOI: 10.1101/2022.05.17.492277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myeloid cell evolution uncovered by shrimp immune cell analysis at single-cell resolution

Abstract: How myeloid cells evolved from invertebrate to vertebrate is still a mystery. Here we collected circulating hemocytes from a marine invertebrate-Penaeus vannamei via gradient centrifugation and identified prohemocyte, monocytic hemocyte and granulocyte as three major types of cells in shrimp hemolymph by single-cell mRNA sequencing. Additional pseudotime trajectory analysis revealed that shrimp monocytic hemocytes and granulocytes were differentiated from a common progenitor which was similar with that of huma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 40 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Under ammonia stress, hemocytes of Penaeus monodon were divided into seven main cell groups ( 124 ). Following stimulation by hemocyte activating factors, hemocytes of L. vannamei were classified into prohemocytes, granulocytes, monocytic hemocytes, transitional cells and germ-like cells ( 125 ). The difference in hemocyte classification results of scRNA-seq might be due to species specificity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under ammonia stress, hemocytes of Penaeus monodon were divided into seven main cell groups ( 124 ). Following stimulation by hemocyte activating factors, hemocytes of L. vannamei were classified into prohemocytes, granulocytes, monocytic hemocytes, transitional cells and germ-like cells ( 125 ). The difference in hemocyte classification results of scRNA-seq might be due to species specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy M. japonicus hemocytes, the cell type that mainly exerts phagocytosis was also not clearly identified ( 73 ). Nevertheless, the hemocytes from treated L. vannamei and P. monodon exhibited cell clusters that exerted phagocytosis ( 124 , 125 ), suggesting that the phagocytic cell types might be differentiated from a particular type of hemocytes, which also indicated that different treatments would lead to the differences of cell clustering.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations